Does erythropoietin protect the preterm brain?. Issue 4 (21st June 2004) - Strunk, T; Härtel, C; Schultz, C
Abstract : There is a high incidence of hypoxic-ischaemic brain injury and intraventricular haemorrhage in newborn infants, particularly those born preterm. Many die during the newborn period or suffer permanent neurodevelopmental handicaps. Hypoxic brain injury develops over several hours and could potentially be influenced by intervention. At present, no drug exists that effectively prevents infant brain injury or ameliorates detrimental neurodevelopmental effects. The hypothesis is put forward that systemic administration of recombinant human erythropoietin positively affects the neurodevelopmental outcome of high risk preterm infants affected by brain injury. A multicentre, randomised, placebo controlled study is proposed to prospectively test this hypothesis.